1996
DOI: 10.1002/hlca.19960790116
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (+)‐Elacomine and (−)‐Isoelacomine, Two Hitherto Unnamed Oxindole Alkaloids from Elaeagnus commutata

Abstract: Racemic elacomine ((%)-2), a hemiterpene spiro oxindole alkaloid from Elueagnus commutata, was synthesized in five steps from 6-methoxytryptamine (19) in 16% overall yield (Scheme 3 ) . The final oxidative rearrangement of the corresponding 8-carboline precursor (%)-21 furnished isoelacomine ((%)-22) as a by-product (6% overall yield). A more elaborate route that started from L-tryptophan furnished (+)-2 and (-)-22 with optical purities of 76% (Scheme 4 ) and established the absolute configuration of these com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
58
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 19 publications
2
58
0
Order By: Relevance
“…The major byproducts were the deiodinated aniline and the saturated lactone 9 (R 1 = Me, R 2 = Boc), which arose from the O-enolate of palladium (Table 1, entry 1). The use of other phosphine ligands, such as bidentate ligands (1,2-bis(diphenylphosphino)ethane (DPPE)), bulky ligands (PA C H T U N G T R E N N U N G (o-tolyl) 3 ), and less electron-donating ligands (PA C H T U N G T R E N N U N G (2-furyl) 3 ), resulted in low yields of the desired product (Table 1, entries 2-4). In the absence of phosphine ligands the reaction gave a complex mixture (Table 1, entry 5).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The major byproducts were the deiodinated aniline and the saturated lactone 9 (R 1 = Me, R 2 = Boc), which arose from the O-enolate of palladium (Table 1, entry 1). The use of other phosphine ligands, such as bidentate ligands (1,2-bis(diphenylphosphino)ethane (DPPE)), bulky ligands (PA C H T U N G T R E N N U N G (o-tolyl) 3 ), and less electron-donating ligands (PA C H T U N G T R E N N U N G (2-furyl) 3 ), resulted in low yields of the desired product (Table 1, entries 2-4). In the absence of phosphine ligands the reaction gave a complex mixture (Table 1, entry 5).…”
Section: Introductionmentioning
confidence: 99%
“…The belimination process might be suppressed under acidic conditions so several acids, which included TfOH, HfA C H T U N G T R E N N U N G (OTf) 4 , and BiA C H T U N G T R E N N U N G (OTf) 3 [19] (Tf = triflate), were investigated in the presence of the DPPF ligand (Table 3, entries 6-8). We found that the addition of BiA C H T U N G T R E N N U N G (OTf) 3 was effective for this domino Pd-catalyzed spirooxindole formation (Table 3, entry 8). The Pd 0 -catalyzed reaction of 17 in the presence of BiA C H T U N G T R E N N U N G (OTf) 3 (10 mol %) provided spirooxindole 18 in 52 % yield with no contamination by diene 19.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations